Analysis of Public Trust and POLRI Performance: An Exploratory Study - Zulganef Zulganef; Irma Nilasari (Universitas Merdeka Malang, 2022)
The purpose of this study is to analyze and understand the relationship of public trust and users loyalty as performance of POLRI institution. This study is carried out by distributing questionnaires (both open-ended and close-ended) on 500 residents in Bandung City, Indonesia, to find out about their perception and trust towards POLRI institution. This study uses quantitative and qualitative approach with descriptive-verificative method to gain deeper information about the phenomena that occurs. This study results in several findings, that the public has good perception of the performance of POLRI in maintaining unity and integrity, handling political and/or legal cases, handling the conditions of public order and security, as well as the handling of COVID-19. However, there is still a need to draw sympathy from the public and gain higher trust from them, which is also suggested in this study.